Analyzing structural and temporal dynamics of the Drosophila cancer studies - Megan McCabe; Qian Tang; Daylon Douglas; Ava Negahdar; Alaina Godbee; Tyrel Ray; Manyun Liu; Kunie Yoshinaga-Sakurai; Andrew Punkay; Dongyu Jia (Medicine, 2026)
Background: Cancer is the 2nd leading cause of human death, and thus an extensive and fast-evolving research field aimed at understanding and curing this disease has developed. Basic science researchers frequently utilize various model organisms to decipher the secrets of cancer, including Drosophila melanogaster . Methods: In this bibliometric analysis study, we extracted and filtered publication data related to Drosophila cancer research from Clarivate’s Web of Science Core Collection from 1990 to 2024, then utilized HistCite and CiteSpace to analyze the collected 2594 published articles. Results: We observed a general trend of increasing growth in the number of publications in the Drosophila cancer research field over the last 35 years. These studies were published by 8867 individual authors from 1678 institutions across 492 journals. We further analyzed the landscape and evolution of their gene, genetics, and cancer modeling research domains, identifying key historically important articles and cancer research domains. We also revealed that the United States, Harvard University, and Perrimon N were the leading contributors in scientific collaboration among countries, institutions, and authors, respectively. Keyword burst analyses further revealed both historical and emerging trends within the Drosophila cancer research field, which are closely related to genes, genetics, and phenotypic traits of tumor studies. Conclusions: In this study, we analyzed the structural and temporal dimensions of Drosophila as a cancer model, offering a comprehensive retrospective of its role, outlining current cancer research areas, and highlighting emerging trends. By examining its historical significance, showing the latest research areas in genes, genetics, and tumor biology, and projecting future research directions, we aimed to shed light on the evolving landscape of the Drosophila model in cancer research.